2016
DOI: 10.1002/cam4.763
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal follicular lymphoma: using primary site as a predictor of survival

Abstract: Gastrointestinal follicular lymphoma (GI‐FL) is a rare extranodal variant of follicular lymphoma (FL) that has been increasingly reported in the literature. An especially indolent course is linked to the disease after a lack of observed patient death in past studies. However, overall survival (OS) and associated prognostic factors remain unclear. A large population‐based database was utilized to identify demographic and clinicopathologic characteristics of GI‐FL, along with survival differences among primary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 39 publications
(102 reference statements)
1
28
0
Order By: Relevance
“…Hence, follow-up evaluation after remission should include whole-body evaluation with PET scan or gallium scintigram. A recent analysis of the Surveillance, Epidemiology, and End Results database in the United States revealed that small intestinal involvement is an independent predictor of longer survival in GI-FL (13).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, follow-up evaluation after remission should include whole-body evaluation with PET scan or gallium scintigram. A recent analysis of the Surveillance, Epidemiology, and End Results database in the United States revealed that small intestinal involvement is an independent predictor of longer survival in GI-FL (13).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that small intestine is involved in 64 to 94% of cases [5]. Contrary to Lebrun and al [7] who found a special predilection of GI-FL in the terminal ileum, most of the latest GI-FL reported affected the duodenum [4,6,8]. But in many studies, small intestine follicular lymphomas have a predominantly multifocal nature.…”
Section: Discussionmentioning
confidence: 93%
“…Usually it's 9+B-cell lymphoma, and the diffuse large B-cell lymphoma (DLBCL) is the most frequent. Follicular lymphoma is the second most common subtype of B-cell lymphoma [2,4]. Primary GI-FL without peripherical lymphadenopathy is very rare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations